2019
DOI: 10.1016/j.addbeh.2018.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Increased attention to the tobacco power wall predicts increased smoking risk among adolescents

Abstract: The purpose of this correlational study was to evaluate the association between attention paid by adolescents to the tobacco power wall and their susceptibility to future smoking. The study was conducted in the RAND Store Lab (RSL), a life-sized replica of a convenience store designed to investigate how tobacco advertising displays in retail point-of-sale environments relate to tobacco use risk and behaviors. In this study, middle and high school students (N = 80) shopped in the RSL while their attention to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In addition, our study considered location to be relative to each photograph, rather than in a defined geographic location within the POS. Although tobacco advertising tends to be consistent in the retail environment, such as in the commonly used Power Wall, value could be added by considering the purely geographic factor in future analyses [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our study considered location to be relative to each photograph, rather than in a defined geographic location within the POS. Although tobacco advertising tends to be consistent in the retail environment, such as in the commonly used Power Wall, value could be added by considering the purely geographic factor in future analyses [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from studies that manipulate exposure to tobacco displays in brick-and-mortar or online stores provides complementary evidence of the rationale for display bans. For example, youth exposed to tobacco ‘power walls’ were more likely to report smoking susceptibility and higher normative perceptions of smoking 79 80…”
Section: Reducing Visibility: Tobacco Point-of-sale Display Bansmentioning
confidence: 99%
“…The retail environment is a key driver of e-cigarette use [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Marketing aims to influence how and why consumers vape [ 28 ] (e.g., perceptions of safety or use for cessation of combustibles [ 29 , 30 , 31 , 32 ], social use, to achieve a “buzz”, for entertainment [ 31 , 32 ]) and to attract new users, promote continued use, and shape perceptions of products and their use [ 21 , 22 , 23 , 24 , 25 ]. This is particularly crucial for newer products, as the ways consumers are first exposed to a product is highly influential on short-term sales or gains [ 33 , 34 ].…”
Section: E-cigarette Retail and Marketingmentioning
confidence: 99%
“…These retail settings are important for several reasons. First, retail settings, including both brick-and-mortar and online, are a prominent, effective source of tobacco advertising in youth [ 24 , 25 , 38 , 39 , 40 , 41 ] and adults [ 42 , 43 , 44 ]. Prior research showed that 68.6% of young adults reported past 30-day e-cigarette advertising/media exposure—most commonly seen on social media (43.4%) and at retailers (31.7%)—and e-cigarette advertising exposure was associated with e-cigarette use [ 45 ].…”
Section: E-cigarette Retail and Marketingmentioning
confidence: 99%